Unraveling the connection between GABA and kisspeptin in the control of reproduction. Issue 6 (June 2019) - Di Giorgio, Noelia P; Bizzozzero-Hiriart, Marianne; Libertun, Carlos; Lux-Lantos, Victoria
Abstract : Neuroendocrine control of reproduction involves the interplay of various factors that become active at some point along development. GnRH is the main neurohormone controlling reproduction and among the most important inputs modulating GnRH synthesis/secretion are GABA and kisspeptins. These interactions of GABA and kisspeptin in the control of GnRH secretion can take place by the presence of the receptors of both factors on the GnRH neuron or alternatively by the actions of GABA on kisspeptin neurons and/or the actions of kisspeptin on GABA neurons. Kisspeptin acts on the Kiss1R, a seven transmembrane domain, Gαq/11 -coupled receptor that activates phospholipase C, although some Gαq/11 -independent pathways in mediating part of the effects of Kiss1R activation have also been proposed. GABA acts through two kinds of receptors, ionotropic GABAA/C receptors involving a chloride channel and associated with fast inhibitory/stimulatory conductance and metabotropic GABAB receptors (GABABR) that are Gi/0 protein linked inducing late slow hyperpolarization. In this review, we aim to summarize the different ways in which these two actors, kisspeptin and GABA, interact to modulate GnRH secretion across the reproductive lifespan.